Analisis Kebutuhan Gim Visual Novel Legenda Ikan Mas Danau Toba - Holong Marisi Simalango (P3M STMIK LIKMI, 2023)
Fairy tales are easier on the mind because they seem to be recorded firmly in human memory. Fairy tales seem reserved for children and are cared for by parents or grandparents with full time at home. Fairy tales such as legends are still entertaining for all ages but are applied with visual media, for example, the Legend of Lake Toba Goldfish. Visual media connected with the advancement of gadget technology is increasing in specifications. Making visual media for legendary fairy tales is applied to Visual Novels. This research aims to analyze the feasibility of the needs of the Lake Toba Goldfish Legend Visual Novel Game with the Quest Preparation stage. This research is still in the needs analysis step based on the Feasibility Study stage, named Quest Preparation, which will enter the development stage. The needs analysis results determined that it has an original storyline or a happy ending. The final result of the analysis is that it has found suitability in functional requirements, storylines, boundaries, schedules, and teams. The game's development stage uses tools, namely Buildbox and a database management system with Firebase.